Pengejawantahan Teori Psikoanalitik pada Etika Bisnis - Shabrina Rahutami Nur Amalia (Jurusan Akuntansi Politeknik Negeri Malang, 2023)
The Embodiment of Psychoanalytic Theory in Business Ethics This article aims to review how the manifestation of psychoanalytic theory in explaining unethical behavior in business organizations is demonstrated through an approach to stakeholder theory. The research method uses literature study. This literature study involves secondary data sources, such as books, journals, previous research articles, mass media, and electronic media. Ten needs of human neurosis according to the psychoanalytic theory of Karen Horney, then classified into five managerial styles formulated by Kats de Vries (1984). Five managerial styles in the company's operations must find stakeholder problems which according to stakeholder theory consist of three main problems. Three major problems with stakeholder theory ultimately lead to five ethical failures. Previous research on fraud has always referred to Sigmund Freud's psychoanalytic theory which is the conscious side of humans. However, by following the path of Karen Horney's psychoanalytic theory that carries the human subconscious side, the understanding of fraud becomes different by considering the needs of human neurosis. This study examines the failure of business ethics from the side of the human subconscious (neurosis). Pengejawantahan Teori Psikoanalitik Pada Etika Bisnis Artikel ini bertujuan untuk meninjau bagaimana manifestasi teori psikoanalitik dalam menjelaskan perilaku tidak etis dalam organisasi bisnis ditunjukkan melalui pendekatan teori pemangku kepentingan. Metode penelitian menggunakan studi literatur. Studi literatur ini melibatkan sumber data sekunder, seperti buku, jurnal, artikel penelitian terdahulu, media massa, dan media elektronik. Sepuluh kebutuhan neurosis manusia menurut teori psikoanalitik Karen Horney, kemudian diklasifikasikan ke dalam lima gaya manajerial yang dirumuskan oleh Kats de Vries (1984). Lima gaya manajerial dalam operasi perusahaan harus menemukan masalah pemangku kepentingan yang menurut teori pemangku kepentingan terdiri dari tiga masalah utama. Tiga masalah utama dengan teori pemangku kepentingan pada akhirnya menyebabkan lima kegagalan etis. Penelitian sebelumnya tentang penipuan selalu mengacu pada teori psikoanalitik Sigmund Freud yang merupakan sisi sadar manusia. Namun, dengan mengikuti jalan teori psikoanalitik Karen Horney yang mengusung sisi bawah sadar manusia, pemahaman tentang penipuan menjadi berbeda dengan mempertimbangkan kebutuhan neurosis manusia. Studi ini mengkaji kegagalan etika bisnis dari sisi alam bawah sadar manusia (neurosis).